BILINGUALISM AND BILINGUAL EXPERIENCES: A CASE OF TWO SOUTHEAST ASIAN FEMALE STUDENTS AT DEAKIN UNIVERSITY - Marlina, Leni (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2016)
BILINGUALISME AND PENGALAMAN BILINGUAL: Sebuah Studi Kasus Dua Mahasiswa Perempuan Asia Tenggara di Deakin UniversityAbstractBilingualism is inseparable from humans’ life. It occurs practically in every country, in all classes of society and in all age groups. Besides, it has many dimensions. This paper is to describe bilingualism dan bilingual experiences from two international students who were studying at Deakin University in 2012.  To describe bilingual experiences students two Southeast Asian female students had been interviewed at Deakin University in 2012.  To explore their detail experiences that might not be accessed during the interview, two questionnaires had been used. Furthermore,  the respondents’ life narrative being bilinguals was written based on the result of the interview and the questionnaires.Additionally, this paper contains some discussions.  Firstly, it describes the respondents’ bilingual experiences: their languages, their countries, their brief history of becoming bilingual, and their family environment in relation to bilingualism.  Secondly, it examines bilinguals’ responses and then applying them for Baker’s (2011a) dimensions of bilingualism and other related theories.  Thirdly, it includes a critical analysis of the socio, political, and educational issues discussed by the respondents in relation to being brought up bilingually.  Last, it includes an analysis on how bilingual experiences shape their identities and view the world.Key words:  bilingualism, bilingual experience, asian female students AbstrakBilingualisme tidak dapat dipisahkan dari kehidupan manusia. Hal ini terjadi secara praktis di setiap negara, di semua kelas masyarakat dan di semua kelompok usia. Selain itu, bilingualisme juga memiliki banyak dimensi. Makalah ini untuk menjelaskan bilingualisme dan pengalaman bilingualis (dwi bahasa) dua siswa internasional yang sedang belajar di Deakin University pada tahun 2012. Untuk menggambarkan pengalaman dwi bahasa, dua siswa perempuan Asia Tenggara telah diwawancarai di Deakin University pada tahun 2012. Untuk mengeksplorasi pengalaman detail mereka yang mungkin tidak dapat diakses selama wawancara, dua kuesioner juga digunakan. Selanjutnya, narasi hidup responden menjadi bilingualis ditulis berdasarkan hasil wawancara dan kuesioner. Selain itu, makalah ini berisi beberapa diskusi. Pertama, menggambarkan pengalaman dwibahasa responden: bahasa mereka, negara mereka, sejarah singkat mereka menjadi penutur dwi bahasa, dan lingkungan keluarga mereka terkait dengan bilingualisme. Kedua, mengkaji tanggapan bilinguals dan kemudian menerapkannya untuk dimensi bilingualisme Baker (2011a) dan teori terkait lainnya. Ketiga, mencakup analisis kritis tentang isu sosio, politik, dan pendidikan yang didiskusikan oleh responden sehubungan dengan diangkat secara bilingual. Terakhir, mencakup analisis tentang bagaimana pengalaman dwibahasa membentuk identitas mereka dan melihat dunia.Key words:  bilingualism, bilingual experience, asian female students